Analisis Penggunaan Aplikasi Siskeudes Dalam Pengelolaan Keuangan di Desa Belapunranga Kec. Parangloe Kab. Gowa Sulawesi Selatan - Ayu Auliyah; Samirah Dunakhir (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2022)
This study aims to determine how well the use of the Siskeudes Application in Financial Management in Belapunranga Village, Kec. Parangloe Kab. Gowa, South Sulawesi. The variable in this study is the use of the Siskeudes Application in Financial Management as measured by Permendagri Number 20 of 2018 concerning Financial Management. The population of this research is Financial Management in Belapunranga Village, Kec. Parangloe Kab. Gowa, South Sulawesi, while the sample in this study used Financial Management Results for the 2021 Fiscal Year. Data collection was carried out using documentation, while the data analysis technique used was descriptive analysis using a rough conformity index measurement. The results showed that the overall use of the Siskeudes Application in Financial Management with 5 indicators namely planning, implementation, administration, reporting, and accountability can still be said to be quite appropriate/good enough with a percentage of 73% from 100%.